Perlindungan Hukum Terhadap Pelaku Usaha UMKM - Ardi Abdillah Rahman; Syaiful Islamiyah; Ziqra Ahmad Fauzi; Yevyna Zolana (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
Micro, small and medium enterprises play an important role in the Indonesian economy, but often experience challenges such as legal protection, access to capital, limited management capabilities and limited market access. The aim of this research is to determine the effect of legal protection received by micro, small and medium enterprises, which really needs attention because micro, small and medium enterprises can encourage Indonesia's economic growth. Some forms of legal protection that can be provided include: Protection of intellectual property rights, such as brands, patents and copyrights, to protect the innovation and creativity of MSME players. Protection against unfair business competition, such as monopoly and monopsony practices, to ensure a fair business climate. Protection of access to capital, such as ease of obtaining credit and capital assistance, to support business growth and development. Protection of market access, such as ease of participating in tenders and government procurement programs for goods/services, to expand business opportunities. Employment protection, such as occupational safety and health guarantees, to ensure employee welfare.